Transtemporal Endoscopic Deep Plane Face Lift - Zekeriya Kul, MD; Erhan Eryilmaz, MD; Emre Özer, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Facial aging involves multifactorial changes affecting the bone, superficial musculoaponeurotic system, fat pads, and skin, primarily manifesting as the downward displacement of these structures. The transtemporal endoscopic deep plane face lift (TEDPF) suggests a vertical lifting method, targeting these issues without a preauricular incision. Methods:. A retrospective study was conducted on 140 patients (133 women and 7 men) 33–67 years of age who underwent TEDPF from February 2020 to March 2023. Of these, 42 patients also received a neck lift. The surgical technique involved endoscopic dissection and vertical lifting and fixation of the superficial musculoaponeurotic system layer using specific suture points. An objective photographic analysis was performed by measuring preoperative and postoperative lower eyelid lengths to assess aesthetic outcomes. Results:. The follow-up period ranged from 18 to 36 months. Temporary frontal neuropraxia occurred in 5 patients, resolving within 3 weeks to 3 months. Revision surgery was required for 6 patients due to excess preauricular skin or temporal skin accumulation malar dimpling. Significant improvements were observed, especially in periorbital, nasolabial, and jowl areas, enhancing eye shape and reducing the need for lower blepharoplasty. Objective photographic analysis showed a significant reduction in lower eyelid length postoperatively, with a mean percentage reduction of 22.45% in eyelid length (P < 0.05). Conclusions:. TEDPF achieves effective vertical lifting for facial rejuvenation, minimizes scarring, and reduces surgery time. It provides notable aesthetic improvements with manageable complications, suitable for patients prone to keloids or seeking less invasive options.